Social conditions of the elderly in the coastal area of Arequipa 2019: A diagnosis before the coronavirus - Huamán Asillo, Luis Daniel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In any part of the world, older adults have the right to dignified, active, caring aging without discrimination. The research shows the characterization of social conditions, before the presence of Covid-19; a reality of insecurity and exclusion, they do not have housing welfare, there is a lack of services and vulnerability in their diet. These difficulties could be reversed, with political decisions for their well-being, changing the negative image of old age. But they were the most affected by the coronavirus pandemic.